2017
DOI: 10.1016/j.eurpsy.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Familial liability to psychosis is a risk factor for multimorbidity in people with psychotic disorders and their unaffected siblings

Abstract: Multimorbidity is a common burden, significantly more prevalent in patients and their unaffected siblings. Familial liability to psychosis showed an independent effect on multimorbidity; gender and age are also important factors determining multimorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 65 publications
(112 reference statements)
0
10
0
Order By: Relevance
“…Due to shared liability genes and clustering of socioenvironmental adversity within families, the risk of developing psychotic disorder is found to be stronger in relatives of patients compared with the general population (Cardno et al, 1999; Linscott & van Os, 2013; van Os et al, 2017). This is also reflected at a phenomenologically and temporally early stage in an increased prevalence of subclinical psychotic symptoms in siblings of patients with a psychotic disorder (Islam et al, 2017; van Os et al, 2017). This begs the question, which processes and mechanisms operate in individuals with increased familial liability in pathways to psychotic disorders (Guloksuz et al, 2019; van Os et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to shared liability genes and clustering of socioenvironmental adversity within families, the risk of developing psychotic disorder is found to be stronger in relatives of patients compared with the general population (Cardno et al, 1999; Linscott & van Os, 2013; van Os et al, 2017). This is also reflected at a phenomenologically and temporally early stage in an increased prevalence of subclinical psychotic symptoms in siblings of patients with a psychotic disorder (Islam et al, 2017; van Os et al, 2017). This begs the question, which processes and mechanisms operate in individuals with increased familial liability in pathways to psychotic disorders (Guloksuz et al, 2019; van Os et al, 2017).…”
mentioning
confidence: 99%
“…There is good evidence that both genetic and socioenvironmental factors increase the risk for psychosis (Guloksuz et al, 2019; Kirkbride et al, 2012; Morgan et al, 2010; van Os et al, 2017). Several twin and family studies have shown that the risk of developing a psychotic disorder is increased in first-degree relatives of patients with the disorder (Guloksuz et al, 2019; van Os et al, 2017), which suggests a familial liability to psychosis (Islam et al, 2017). Due to shared liability genes and clustering of socioenvironmental adversity within families, the risk of developing psychotic disorder is found to be stronger in relatives of patients compared with the general population (Cardno et al, 1999; Linscott & van Os, 2013; van Os et al, 2017).…”
mentioning
confidence: 99%
“…Evidence for familial liability to psychosis [ 16 - 18 ] shows that first-degree relatives of patients with psychosis have an increased risk of developing psychotic disorders [ 17 , 19 ]. In addition, although exposure to childhood trauma is higher in patients with psychotic disorders, patients and their siblings share a degree of exposure to childhood trauma [ 20 ], as they also share many sociodemographic, parental, and developmental characteristics [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Psychometric risk states can be characterized by nonspecific distress and attenuated symptoms that are not disorder specific, thereby implying a transdiagnostic perspective on early stages of mental disorders [ 4 , 6 , 7 ]. In addition, there is evidence for an increased familial liability to severe mental disorders, such as psychosis [ 8 ] and major depression [ 9 , 10 ], suggesting that even relatives without a formal diagnosis of a disorder can be placed closer toward clinical thresholds on the continuum of mental health.…”
Section: Introductionmentioning
confidence: 99%